2022
DOI: 10.1016/j.cjco.2022.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Activity Levels and Sitting Time of Adults Living With Atrial Fibrillation: The CHAMPLAIN-AF Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…[20][21][22][23] For instance, positive outcome expectations (eg, manage better irregular heart rhythm if physically active) and high task selfefficacy (ie, confidence to engage in MVPA) have been shown to be significantly associated with increased PA in physically inactive adults and individuals with CVD, respectively. 24,25 In patients living with AF, our CHAMPLAIN-AF study 15 found that most patients had positive outcome expectations and moderate confidence to engage in PA. Moreover, we found significant positive relationships in outcome expectations, task self-efficacy, and PA levels and sitting time.…”
Section: What Is Novel?mentioning
confidence: 89%
See 3 more Smart Citations
“…[20][21][22][23] For instance, positive outcome expectations (eg, manage better irregular heart rhythm if physically active) and high task selfefficacy (ie, confidence to engage in MVPA) have been shown to be significantly associated with increased PA in physically inactive adults and individuals with CVD, respectively. 24,25 In patients living with AF, our CHAMPLAIN-AF study 15 found that most patients had positive outcome expectations and moderate confidence to engage in PA. Moreover, we found significant positive relationships in outcome expectations, task self-efficacy, and PA levels and sitting time.…”
Section: What Is Novel?mentioning
confidence: 89%
“…This was a subanalysis of the CHAMPLAIN-AF 15 study which included patients living with AF within the Champlain Local Health Integration Network of Eastern Ontario, Canada. Briefly, this was an observational cohort study to determine the MVPA levels and sitting time of patients living with AF and its association between outcome expectations or task self-efficacy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When compared to traditional resistance training, the inclusion of additional intra-set, inter-repetition or distributed rest periods in interval resistance training may mitigate fatigue, improve the patient’s perception of resistance exercise and importantly reduce the haemodynamic response and cardiac load [ 19 ]. Such benefits are particularly important for cardiac patients as many present with poor exercise tolerance, low task-self efficacy regarding resistance exercise [ 87 ], and in some cases possible hypertensive responses to exercise.…”
Section: The Benefits Utility and Limitations Of Interval Resistance ...mentioning
confidence: 99%